MGMT promoter methylation in triple negative breast cancer of the GeparSixto trial - Jank, Paul; Gehlhaar, Claire; Lederer, Bianca; Fontanella, Caterina; Schneeweiss, Andreas; Karn, Thomas; Marmé, Frederik; Sinn, Peter; Mackelenbergh, Marion van; Sinn, Bruno; Zahm, Dirk-Michael; Ingold-Heppner, Barbara; et al. (PLOS ONE, 2020)
Triple-negative breast cancer (TNBC) is typically treated with chemotherapeutic agents, including carboplatin (Cb), an DNA platinating agent. The O6-methylguanine-DNA-methyltransferase gene (MGMT) encodes for the protein O6-alkylguanine-DNA-alkyltransferase (MGMT protein). MGMT protein is involved in DNA repair mechanisms to remove mutagenic and cytotoxic adducts from O6-guanine in DNA. In glioblastoma multiforme, MGMT methylation status is a predictive biomarker for increased response to temozolomide therapy. It has been suggested, that MGMT protein may have relevance for cellular adaptation and could have an influence on resistance to carboplatin therapy. We investigated the influence of MGMT promoter methylation on pathologic complete response and survival of patients with TNBC treated in the neoadjuvant GeparSixto trial. In 174 of 210 available TNBC tumors a valid MGMT promoter methylation status was determined by pyrosequencing of 5 CpG islands. In 21.8%, we detected a mean MGMT promoter methylation >10%. Overall, MGMT promoter methylation was not significantly associated with pathological complete response (pCR) rate. After stratification for the two therapy arms with and without Cb no statistically significant differences in therapy response rates between the two MGMT promoter methylation groups could be observed. Our results show that different MGMT promoter methylation status is not related to different chemotherapy response rates in the TNBC setting in GeparSixto.
Gesehen am 29.10.2020